Profile of the scientific production in workers’ health - Bezerra, Marcio Luís Soares; Neves, Eduardo Borba (Saúde e Sociedade, 2010)
This study aimed to outline the profile of the scientific literature on workers' health in the period between 2001 and March 2008. The research was conducted through the electronic search of papers indexed in the database Scientific Electronic Library Online (SciELO) with the descriptors "workers' health" and "occupational health". Overall, 170 complete papers were analyzed. The journal Cadernos de Saúde Pública was the source that published most papers (35,29%), followed by Ciência & Saúde Coletiva (16,47%). The quantitative method was used by 53.52% of the papers, conceptual discussions about Health-Environment-Work relations were the most frequent object of study (40.59%), and health professionals were the most studied population (20,59%). It was also verified that Brazil's scientific production on the theme is concentrated in the Southeast (69,66%). The increase in scientific production in the field of workers' health has followed the growth tendency of the national scientific production in the last 8 years. The study shows that the potential growth of this field is compatible with the demand for knowledge of public policies managers who work with Health-Environment-Work relations.